Bacteremia due to Leuconostoc pseudomesenteroides in a Patient with Acute Lymphoblastic Leukemia: Case Report and Review of the Literature. (22nd August 2016) - Ino, Kazuko; Nakase, Kazunori; Suzuki, Kei; Nakamura, Akiko; Fujieda, Atsushi; Katayama, Naoyuki
Abstract : Leuconostoc species are vancomycin-resistant Gram-positive cocci. Infections due to Leuconostoc species have been reported in various immunocompromised patients, but little is known about such infection in patients with hematologic malignancies. We report a case of Leuconostoc infection in a 44-year-old woman with acute lymphoblastic leukemia. The patient developed a high fever despite antimicrobial therapy with doripenem after induction chemotherapy. After an isolate from blood cultures was identified as L. pseudomesenteroides, we changed the antibiotics to piperacillin-tazobactam and gentamicin, after which the patient recovered from the infection. Physicians should be aware of Leuconostoc species as causative pathogen if they encounter Gram-positive cocci bacteremia resistant to standard antibiotics such as vancomycin and teicoplanin, especially in patients with hematologic malignancies.